[18F]FDG PET/CT Studies in Transgenic Hualpha-Syn (A53T) Parkinson’s Disease Mouse Model of α-Synucleinopathy - Mondal, Rommani; Campoy, Anthony-David Tawatao; Liang, Christopher; Mukherjee, Jogeshwar (Frontiers in Neuroscience, 2021)
Transgenic mice that express the A53T mutant Alpha-synuclein protein at six times the level of endogenous mice Alpha-synuclein are a model of Alpha-synucleinopathy found in Parkinson’s disease (PD). This Hualpha-Syn(A53T) PD model is useful in assessing non-motor deficits at earlier stages of onset of PD. We report findings on metabolic changes using [18F]FDG PET/CT in the Hualpha-Syn(A53T) PD mouse model in comparison to non-carrier mice. Whole-body PET/CT imaging of male and female mice were carried out 2 hours after [18F]FDG ip administration under 3% isoflurane anesthesia. Brain images were analyzed with PET images coregistered to a mouse brain MRI template. Hualpha-Syn(A53T) mice had significantly lower [18F]FDG uptake in several brain regions compared to the no-carrier mice. Significant hind limb muscle [18F]FDG hypometabolism at 9 months of age in A53T PD mice was also indicative of neurodegenerative disease, with a progressive motoric dysfunction leading to death. Significant decrease (up to 30%) in [18F]FDG uptake were observed in 9-month old male and female Hualpha-Syn(A53) mice. This is consistent with the cortical hypometabolism in PD patients. Hualpha-Syn(A53) mice may thus be a suitable model for studies related to PD Alpha-synucleinopathy for the discovery of new biomarkers.